Produksi Benih Strain Mutiara (Clarias Gariepinus Burchell, 1822) Melalui Pemijahan Butan Pada Unit Pembenihan Ikan Unggul Farm - Nur Asiah; Henni Syawal; Eni Yulinda; Yuliati Yuliati; Yetti Elfina S (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The purpose of this community service activity is to transfer knowledge and technology about artificial spawning of Mutiara Strain (Clarias gariepinus Burchell, 1822) to the Unggul Farm fish hatchery unit in Pangkalan Baru Village, Kec. Siak Hulu Regency. Kampar. This activity will be held on July 12 – August 12, 2021. The method used is direct demonstration and active participation. The spawning-stimulating hormone was Ovaprim with a dose of 0.5 ml/kg female broodstock and 0.3 ml/kg male broodstock. Artificial spawning, which is the process of removing eggs and sperm by stripping and surgery, so that the maximum number of eggs and sperm is obtained. Then fertilization is carried out, and then the eggs are incubated until they hatch which are called larvae. Artificial spawning produces larvae as many as 3 tanks with a size of 1 X 5.5 m. Natural spawning is carried out by the Unggul Farm fish hatchery unit each spawning period producing one larval tank with a size of 1 X 5.5 m. The benefits of artificial spawning are to increase the production of Mutiara strain seeds and improve the welfare of members of the Unggul Farm fish hatchery unit